Varietal Differences in Food Value of Leaf Blight Infected Mulberry Leaves and their Impact on Economic Characters of Silkworm (Bombyx mori L.) (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Mulberry; nutritional food value; leaf blight disease; Phyllosticta sp.; silkwormBangladesh j. genet. biotechnol. 5 (1&2): 73-77, 2004 (June & December)